2018
DOI: 10.1111/apt.15010
|View full text |Cite
|
Sign up to set email alerts
|

The risk of venous thromboembolism during and after hospitalisation in patients with inflammatory bowel disease activity

Abstract: Summary Background Inflammatory bowel disease (IBD) increases the risk of venous thromboembolism. Aims To determine when patients are at high risk of thromboembolic events, including after major surgery, and to guide timing of thromboprophylaxis. Methods Each IBD patient from Clinical Practice Research Datalink, linked with Hospital Episode Statistics, was matched to up to five non‐IBD patients in this cohort study. We examined their risk of thromboembolism in hospital and within 6 weeks after leaving hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…We are delighted by the interest shown in our paper by Ding et al 1,2 We would agree with Ding et al that having identified patients from records of healthcare in the UK for our analysis, our results are only generalisable to this population with certainty. We would expect, however, that they could be generalised to populations with similar features and living in areas with comparable healthcare systems.…”
Section: Editorssupporting
confidence: 70%
See 1 more Smart Citation
“…We are delighted by the interest shown in our paper by Ding et al 1,2 We would agree with Ding et al that having identified patients from records of healthcare in the UK for our analysis, our results are only generalisable to this population with certainty. We would expect, however, that they could be generalised to populations with similar features and living in areas with comparable healthcare systems.…”
Section: Editorssupporting
confidence: 70%
“…For instance, data from a recent study showed that although East Asian IBD patients carried 2-fold increased risk of VTE, the incidence of VTE in that population was lower than that in Western countries, which might imply a different strategy. 2 Secondly, the incidence of VTE in UC patients was significantly higher than those with Crohn's disease 3 but the percentage of UC in the enrolled IBD patients was not provided. And lastly Chu et al pointed out the potential increased risk sustained even after the patients had left hospital, but did not look into the underlying mechanism.…”
Section: Editorsmentioning
confidence: 99%
“…This study and others have led to consensus guidelines recommending thromboprophylaxis during hospitalisation but not in the ambulatory setting . In a recent administrative database study from the UK, the risk of VTE within 6 weeks post‐discharge was 19.7 and 12.3 per 1000 person years for post‐surgical and medical IBD patients respectively, suggesting that the post‐discharge period may remain a vulnerable period for IBD patients . In previous studies involving high‐risk hospitalised patients with medical illness who did not receive extended thromboprophylaxis, the reported rates of symptomatic VTE ranged from 0.75% to 1.5% within 45 days of discharge .…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the post‐discharge setting likely remains a vulnerable period for patients with IBD. A recent study using health administrative date found a substantial risk of VTE following discharge in medical and surgical IBD patients; however, patients were only followed for a total of 6 weeks and potential risk factors for VTE were not assessed . Given the paucity of literature in this area, our aims were to assess the incidence and risk factors for VTE in IBD patients in the post‐discharge setting and to create a simple point of care risk stratification tool to guide prophylaxis decisions in the post‐discharge setting.…”
Section: Introductionmentioning
confidence: 99%
“…In their paper, King et al, show an adjusted hazard ratio of 1.4 for developing colorectal cancer for those with ulcerative colitis. The risk of other significant and potentially fatal complications of IBD such as other cancers (both related to IBD and its treatment), venous thromboembolism, malabsorption, poor mental health and infection has been addressed elsewhere 3‐6 …”
mentioning
confidence: 99%